A dimeric urea of the bisabolene sesquiterpene from the Okinawan marine sponge Axinyssa sp. inhibits protein tyrosine phosphatase 1B activity in Huh-7 human hepatoma cells. Issue 2 (15th January 2016) - Abdjul, Delfly B.; Kanno, Syu-ichi; Yamazaki, Hiroyuki; Ukai, Kazuyo; Namikoshi, Michio
Graphical abstract: Abstract: Protein tyrosine phosphatase 1B (PTP1B) plays an important role as a negative regulator of the insulin and leptin signaling pathways. Therefore, this enzyme is regarded as an attractive therapeutic target for the treatment of type 2 diabetes and obesity. Our screening program for PTP1B inhibitors led to the isolation of four sesquiterpenes and sterol: N, N ′-bis[(6 R, 7 S )-7-amino-7, 8-dihydro-α-bisabolen-7-yl]urea (1 ), (6 R, 7 S )-7-amino-7, 8-dihydro-α-bisabolene (2 ), (1 R, 6 S, 7 S, 10 S )-10-isothiocyanato-4-amorphene (3 ), axinisothiocyanate J (4 ), and axinysterol (5 ) from the marine sponge Axinyssa sp. collected at Iriomote Island. Of these, compound1 was the most potent inhibitor of PTP1B activity (IC50 = 1.9 μM) without cytotoxicity at 50 μM in two human cancer cell lines, hepatoma Huh-7 and bladder carcinoma EJ-1 cells. Compound1 also moderately enhanced the insulin-stimulated phosphorylation levels of Akt in Huh-7 cells. Therefore, compound1 has potential as a new type of anti-diabetic drug candidate possessing PTP1B inhibitory activity.